A Gamified Assessment Tool to Enhance Learning Motivation in History - Fahruddin; Arif Saefudin (LPPM Undiksha, 2025)
Low student motivation in history subjects often leads to minimal participation and superficial understanding of the material. To address this, the study aimed to develop and evaluate a gamified assessment tool designed to enhance student motivation in learning history. Gamification, incorporating elements such as points, badges, and leaderboards, has been shown to increase motivation and engagement across various fields; however, its application in history assessments remains relatively unexplored. This research followed the Research and Development method, utilizing the ADDIE model. In the Analysis phase, data were gathered through surveys and interviews with teachers and students. The Design phase focused on creating the assessment tool with gamified features. In the Development phase, a prototype was created and validated by experts in history and media. The Implementation phase involved testing the tool with 10th and 11th-grade students. Data were collected through surveys, interviews, and classroom observations. Results demonstrated that the gamified assessment tool significantly improved students' motivation, with the average score increasing from 3.2 to 4.5, notably enhancing interest, engagement, and learning satisfaction. The final evaluation confirmed that the tool not only boosted motivation but also deepened students' understanding of historical content. This tool can be adapted for use by educators in Indonesia to address similar challenges in history education and can be extended to other subjects to enhance overall educational quality.